A highly sensitive naphthaoxazole-based cell-permeable ratiometric chemodosimeter for hydrazine. Issue 97 (4th October 2016) - Shweta,; Kumar, Ajit; Neeraj,; Asthana, Sharad Kumar; Prakash, Anand; Roy, Jagat Kumar; Tiwari, Ida; Upadhyay, K. K.
Abstract : The present communication reports a ratiometric chemodosimeter (P1 ) for the efficient detection of hydrazine down to a lowest level of 1.79 × 10 −9 M. Abstract : The environmental toxicity, detonable characteristics and widespread usage of hydrazine in industrial activities, coupled with the fact that it is a leading candidate as a hydrogen reservoir, mean that selective methods for the detection of trace levels of hydrazine are much needed. We report herein a ratiometric chemodosimeter (P1 ) for the highly efficient detection of hydrazine at a lowest level of 1.79 × 10 −9 M. TheP1 probe was designed by the judicious anchoring of a naphthaoxazole skeleton to malononitrile. The same chemodosimeter also enables the bioimaging of hydrazine in live cells. The performance ofP1 was tested in the form of test paper strips, as well as in the solid state for the identification of hydrazine vapours. The sensing mechanism was established through spectroscopic techniques and was further fortified through theoretical calculations using density functional theory.